If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3(4x-8)=7(2x+6)
We move all terms to the left:
3(4x-8)-(7(2x+6))=0
We multiply parentheses
12x-(7(2x+6))-24=0
We calculate terms in parentheses: -(7(2x+6)), so:We get rid of parentheses
7(2x+6)
We multiply parentheses
14x+42
Back to the equation:
-(14x+42)
12x-14x-42-24=0
We add all the numbers together, and all the variables
-2x-66=0
We move all terms containing x to the left, all other terms to the right
-2x=66
x=66/-2
x=-33
| 32y-15y=-7 | | 8y-5/7y+1=5/4 | | -3x-86=89-8x | | 4+2u=14 | | √6x+16=x | | 7m+12=3m+4 | | (x-0.04x)=2.12 | | 3(2x+4)-1=2(3x-9)+2 | | 2x-89=175-9x | | 16=8+2h | | 5(c-1)^2=40 | | 6=3n*5 | | 5(3x+2)=-3(3x-5) | | 14+8x=6x-12x | | 2+(x+5)^1/2=x | | 5u-104=881 | | 1/2x+16=38 | | 6a+28-10a=32 | | 4x-138=13x+87 | | r-775/21=6 | | 34=-6=5x | | 5(x-2)+6=-29 | | -5=4+3y | | 23(y+39)=989 | | (0.40)200x=900 | | 19b+32=583 | | -r^2=6r-2=7 | | -17=2v-3 | | 24+2x=3x+2(2*4) | | -52+12x=4x+92 | | 34^2=18^2+x^2 | | 28b-9=747 |